BRANDING SUSTAINABLE FOREST CITY AT IBU KOTA NEGARA (IKN) NUSANTARA VIEWED FROM THE PERCEPTION OF PENTAHELIX STAKEHOLDERS IN MANADO CITY - Felly Ferol Warouw; Piet Hein Pusung; Heri Herdiawanto; R. Mokhamad Luthfi (Universitas Trisakti, 2024)
Aim: This research aims to find the perceptions of these stakeholders towards sustainable forest city branding in the relocation of the Ibu Kota Negara-IKN (National Capital City) of the Nusantara (archipelago) to Kalimantan through a study in Manado City as one of the buffer cities of the IKN Nusantara. Methodology and Results: The research method is descriptive and justified by correlational research method. The population in this study were stakeholders involved in urban life activities from various backgrounds. A sample of 30 respondents representing urban pentahelix stakeholders residing in the city of Manado was identified randomly and determined purposively. This research is conducted on the existing city pentahelix stakeholders and encourages the sustainability of development and the city environment itself. Conclusion, significance, and impact study: The results showed that pentahelix stakeholders' understanding of sustainable forest city branding is understood by all pentahelix-based stakeholders. At the next level, whether these stakeholders understand and agree to implement what the sustainable forest city program is, the level of agreement of the respondents is above 70 percent. But then whether the content of sustainable forest city branding already exists, there is a decrease in understanding by these stakeholders. For this reason, intervention is needed in the form of socialization of more massive sustainable forest city branding so that it is understood by each pentahelix stakeholder so that collaboration can be improved with the hope of being able to improve the quality of the IKN itself and the surrounding cities of this IKN.